Rapid increase in the risk of heat-related mortality - Lüthi, Samuel; Fairless, Christopher; Fischer, Erich M; Scovronick, Noah; Ben Armstrong; Coelho, Micheline De Sousa Zanotti Stagliorio; Guo, Yue Leon; Guo, Yuming; Honda, Yasushi; Huber, Veronika; Kyselý, Jan; Lavigne, Eric; et al. (Nature communications, 2023)
Heat-related mortality has been identified as one of the key climate extremes posing a risk to human health. Current research focuses largely on how heat mortality increases with mean global temperature rise, but it is unclear how much climate change will increase the frequency and severity of extreme summer seasons with high impact on human health. In this probabilistic analysis, we combined empirical heat-mortality relationships for 748 locations from 47 countries with climate model large ensemble data to identify probable past and future highly impactful summer seasons. Across most locations, heat mortality counts of a 1-in-100 year season in the climate of 2000 would be expected once every ten to twenty years in the climate of 2020. These return periods are projected to further shorten under warming levels of 1.5 °C and 2 °C, where heat-mortality extremes of the past climate will eventually become commonplace if no adaptation occurs. Our findings highlight the urgent need for strong mitigation and adaptation to reduce impacts on human lives.
Keywords: vysoká teplota; Biodiversity; Temperature; klimatické změny; biodiverzita; Climate Change; teplota; Hot Temperature; lidé; Humans; aklimatizace; Acclimatization